IMPROVEMENT OF THE QUALITY OF PUMPING GROUP CASTINGS - D. M. Kukui; f I. Rudnicki; J. A. Nikolaichik; L. V. Sudnik; N. V. Romanova (Литьë и металлургия)
The main results of changing of high-strength antipenetration coatings in the result of development of the potentialities of their main component – refractory filler are given.